Svetozar Marković (1846–1875) in the culture of remembrance among the Serbs - Elezović, Zvezdana (Sociološki pregled, 2026)
The author of the paper explores Svetozar Marković’s place in the culture of remembrance among the Serbs, with a special overview of institutional and monumental forms preserving and shaping his historical and symbolic significance. One of the most prominent persons of the Serbian socialist thought and democratic tradition of the 19th century, Marković has become an important and permanent symbol of social engagement, enlightenment and the idea of social justice. Numerous institutions in Serbia have been named after him – from educational and cultural institutions, such as the University Library “Svetozar Marković” in Belgrade, to the town of Svetozarevo (today’s Jagodina) – which proves the breadth and permanence of his place in collective memory. Svetozar Marković’s bust in front of the University Library in Belgrade stands as a symbol of academic and ideological tradition established by him. Starting from the theoretical postulates of the culture of remembrance, this paper will show that Marković’s person has been an object of different ideological interpretations ion the public discourse, depending on the historical context.
Keywords: Svetozar Marković (1846–1875); culture of remembrance; memory; ideas; Serbs